2023
DOI: 10.1126/scirobotics.ade2184
|View full text |Cite
|
Sign up to set email alerts
|

Soft robotic patient-specific hydrodynamic model of aortic stenosis and ventricular remodeling

Abstract: Aortic stenosis (AS) affects about 1.5 million people in the United States and is associated with a 5-year survival rate of 20% if untreated. In these patients, aortic valve replacement is performed to restore adequate hemodynamics and alleviate symptoms. The development of next-generation prosthetic aortic valves seeks to provide enhanced hemodynamic performance, durability, and long-term safety, emphasizing the need for high-fidelity testing platforms for these devices. We propose a soft robotic model that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The soft robotic left ventricle is implemented and controlled to represent patient-specific data in a high-fidelity anatomical model. The integration of a controllable soft robotic left ventricle into a cardiovascular simulator is a critical step forward toward the development of clinically relevant hemodynamic and biomechanical models personalizable to patient-specific conditions 27 ranging from stiff left ventricles with a small cavity and a restrictive pattern of diastolic function, as in the HFpEF patient, to large ventricles with a predominately systolic dysfunction, as in dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soft robotic left ventricle is implemented and controlled to represent patient-specific data in a high-fidelity anatomical model. The integration of a controllable soft robotic left ventricle into a cardiovascular simulator is a critical step forward toward the development of clinically relevant hemodynamic and biomechanical models personalizable to patient-specific conditions 27 ranging from stiff left ventricles with a small cavity and a restrictive pattern of diastolic function, as in the HFpEF patient, to large ventricles with a predominately systolic dysfunction, as in dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…While this setup achieves a good level of realism, the use of an animal heart restricts the simulation to non-patient-specific scenarios. Rosalia et al 27 used a silicon left ventricle with a soft robotic sleeve to replicate systolic contraction by compressing the element externally. Such a method could reproduce waveforms in agreement with in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Validated through echocardiographic and catheterization techniques, this model offers superior controllability compared to rigid systems, ensuring a physiological representation of cardiac function. In addition, this model was tested in different backgrounds, presenting consistent results in the assessment of the hemodynamic efficacy of TAVI [52].…”
Section: Aortic Valvementioning
confidence: 96%
“…[51] In previous studies, we demonstrated the ability of the LV sleeve to limit cardiac filling in an in vitro model of aortic stenosis and that of the aortic sleeve to recreate the hemodynamics of pressure overload in vitro and in vivo. [52,53] Here, we redesign the LV sleeve for the development of a porcine model of HFpEF capable of tuning pressure overload and ventricular compliance independently, in a facile, immediate, tunable manner, which allows us to re-create a broad spectrum of HFpEF hemodynamics. By investigating the hemodynamic response of the model postimplantation of an interatrial shunt device, we then demonstrate the applicability of this model for in vivo evaluation of devicebased solutions for HFpEF (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%